Bibliometric Analysis of The Use of Science Learning Media In Elementary Schools During A Decade - Anggun Taruna Puspitasari; Wahono Widodo; Dian Permatasari Kusuma Dayu (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
This research uses a bibliometric approach to examine how science learning media have been used in elementary schools over the last ten years. The data source used is Dimension AI, with the keywords "science learning media" and "primary school," in the publication range from 2014 to 2024. This research utilizes VOSviewer software to visualize author collaboration patterns, main research topics, and the learning media most frequently used in the study. The results of the analysis show a significant increase in the number of publications related to science learning media in that time period, with a peak in 2023. Additionally, this research found that technology-based learning resources, such as interactive and digital media, function well, dominating research trends. Apart from that, the main themes that are often discussed include the development of digital-based learning tools, student involvement in the learning process, and the effectiveness of using manipulative and interactive media. A trend of increasing collaboration has occurred in recent years, according to the authors' collaboration analysis, indicating that a number of academics and institutions continue to contribute to this field. According to these findings, this research provides important implications for the development of science learning media in the future, especially in improving learning technology and teacher training to utilize this media optimally. Future development steps include the use of technology such as AR and VR, as well as further development of manipulative media that is in line with the learning context in elementary schools